Cross-Talk Between Tumor Cells Undergoing Epithelial to Mesenchymal Transition and Natural Killer Cells in Tumor Microenvironment in Colorectal Cancer - Vuletić, Ana; Mirjačić Martinović, Katarina; Tišma Miletić, Nevena; Zoidakis, Jerome; Castellvi-Bel, Sergi; Čavić, Milena (Frontiers in Cell and Developmental Biology, 2021)
Tumor cells undergoing epithelial to mesenchymal transition (EMT) and immune cells in tumor microenvironment (TME) reciprocally influence each other. Immune cells, by supplying TME with bioactive molecules including cytokines, chemokines, enzymes, metabolites, and by physical interactions with tumor cells via their receptors, represent an important factor that affects EMT. Chronical inflammation in TME favorizes tumor growth and invasiveness and stimulates synthesis of EMT promoting transcription factors. Natural killer (NK) cells, owing to their unique ability to exert cytotoxic function independent of major histocompatibility (MHC)-mediated antigen presentation, play a significant role in the control of metastasis in colorectal cancer (CRC). Although, the cross-talk between immune cells and tumor cells in general favors the induction of EMT and inhibition of antitumor immune responses, there are some changes in the immunogenicity of tumor cells during EMT of CRC cells that increase their susceptibility to NK cell cytotoxic lysis. However, suppressive TME downmodulates the expression of activating NK cell receptors, decreases the expression of activating and increases the expression of inhibitory NK cell ligands on tumor cells, and impairs NK cell metabolism that altogether negatively affects the overall NK cell function. Furthermore, process of EMT is often associated with increased expression of programmed cell death ligand (PD-L) and expression of immune checkpoint molecules PD-1, TIGIT, and TIM3 on functionally exhausted NK cells in TME in CRC. In this review we discuss modalities of cross-talk between tumor cells and NK cells, with regard of EMT-driven changes.